VIEWS OF SMES IN TURKEY ON ADAPTATION TO BLOCKCHAIN TECHNOLOGY (Third Sector Social Economic Review, 2024)
According to 2020 data, There are about 3,2 million SMEs in Turkey; and these enterprises employ about 11,5 million people. Therefore, SMEs are very importan for Turkey's economy. As well as all over the World, interest in the crypto currency is increasing every day in Turkey.  Therefore, this article aims to examine the internal and external factors that influence the intention to adopt cryptocurrency payments among SME’s. In this study, one-way analysis of variance test for unrelated measurements, t-test, and LSD test for multiple comparisons were used to examine whether there is a significant relationship between SMEs views on blockchain technology and the factors affecting blockchain technology adoption. As a result of the study; It has been determined that there is no significant relationship between the adaptation of Blockchain Technologies and demographic variables such as company type, sector in which the companies operate and company age; except the desire to use blockchain technologies in the future and the type of bank used. There is a statistically significant and positive but weak relationship between the innovation and self-efficacy variables; and  there is a positive and strong relationship between strategic orientation, social impact, perceived usefulness and perceived ease of use variables.
Keywords: Blockchain; SME’s View On Blockchain Technology Adoption Behavior; Adaptatıon Of Blockchaın Technology; SME’s; Turkey